Screw-withdrawal properties of batai (Parensenthes falcataria) particleboard / Safura Mamat, Nurrohana Ahmad and Jamaludin Kasim - Mamat, Safura; Ahmad, Nurrohana; Kasim, Jamaludin (2011)
In this study batai (Parensenthes falcataria) was use as raw material for the production of particleboard and its screw withdrawal properties was determined Particleboard with sizes of 35 x 35 x 12 mm and a target density of 550 kgm-3 was produced with I % wax addition. Results of the study showed that only resin content showed significant effects on the screw withdrawal properties. Particleboards of core particle size of 1.0 mm and 2.0 mm showed no significant influences on screw withdrawal test. Boards made with/without wax addition also showed no significant influence on screw withdrawal property. In conclusions, all particleboards produced from batai wood failed to meet the strength requirements specified in JIS A 5908.